PENGARUH LIKUIDITAS, PROFITABILITAS, DAN UKURAN PERUSAHAAN TERHADAP KEBIJAKAN DIVIDEN DAN HARGA SAHAM (Studi kasus pada Perusahaan Manufaktur Yang Terdaftar di Bursa Efek Indonesia tahun 2013-2017) - Darmawan, Akhmad; Widyasmara, Meriska Yogi; Rejeki, Sri; Aris, Muhammad Rizqie; Yasin, Roqi (Derivatif : Jurnal Manajemen, 2019)
The purpose of this study was to examine the effect of liquidity ratios, profitability and firm size on stock prices with dividend policy as an intervening variable in manufacturing companies listed on the IDX. The sample used in this study are 22 companies with the 2013-2017 research year. The sampling technique uses purposive sampling. Data analysis techniques used descriptive statistics, classical assumption tests, multiple linear regression and sobel tests. The results of this study indicate that liquidity has no effect on dividend policy, liquidity has no effect stock prices, profitability do not affect on dividend policy, profitability has no effect on stock prices, while firm size has significant positive effects on dividend policy and stock price, dividend policy does not affect stock prices, dividend policy is not able to mediate liquidity, profitability and size of the company against stock pricesÂ Keywords: Liquidity, Profitability, Company Size, Stock Price, Dividend Policy